The Effect of Manual Acupressure (Point BL32) on Pain Associated with Intramuscular Injections of Magnesium Sulfate - Seyed S. Najafi; Setareh Nazaribin; Marzieh Momennasab; Amin Kordi Yoosefinejad (Medical Association of Pharmacopuncture Institute, 2019)
The aim of this study was determining the effect of acupressure on the severity of pain associated with intramuscular injections of magnesium sulfate administered by the Z-track technique in patients with eclampsia and preeclampsia. Forty-eight patients participated in this single-group clinical trial, which was conducted in three stages. For each patient, three intramuscular injections were administered by the Z-track technique. The first injection was administered by the conventional method. The second injection at a sham control point and the third injection using acupressure (BL32) were administered. Pain severity was measured on a visual analogue scale. The mean pain intensity was 7.22 in the first, 4.75 in the second and 1.94 in the third injections (p < 0.001). The results of the study showed that acupressure at the BL32 point before intramuscular injection of magnesium sulfate significantly reduced the injection-related pain. Keywords: acupressure, eclampsia, intramuscular, magnesium sulfate, pain, Z-track technique